Microgrids : architectures and control - Hatziargyriou, Nikos; IEEE Xplore (Online Service); Wiley ([Hoboken, New Hersey] : Wiley, 2014)
Microgrids are the most innovative area in the electric power industry today. Future microgrids could exist as energy-balanced cells within existing power distribution grids or stand-alone power networks within small communities. A definitive presentation on all aspects of microgrids, this text examines the operation of microgrids - their control concepts and advanced architectures including multi-microgrids. It takes a logical approach to overview the purpose and the technical aspects of microgrids, discussing the social, economic and environmental benefits to power system operation.
3.4 Implications of Line Parameters on Frequency and Voltage Droop Concepts; 3.4.1 Power Transmission in the LV Grid; 3.4.2 Comparison of Droop Concepts at the LV Level; 3.4.3 Indirect Operation of Droops; 3.5 Development and Evaluation of Innovative Local Controls to Improve Stability; 3.5.1 Control Algorithm; 3.5.2 Stability in Islanded Mode; 3.5.3 Stability in Interconnected Operation; 3.6 Conclusions; References; 4 Microgrid Protection; 4.1 Introduction; 4.2 Challenges for Microgrid Protection; 4.2.1 Distribution System Protection; 4.2.2 Over-Current Distribution Feeder Protection
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Smart power grids; Small power production facilities; Electronic books